Teenagers in Face of the War in Ukraine: Experience of Lithuanians - Lesinskienė, Sigita; Lapinskaitė, Augustė; Česnauskaitė, Augustė (Acta medica Lituanica, 2026)
Background: The war in Ukraine, starting on February 24, 2022, shocked Lithuanians who actively support Ukraine and who are still experiencing the threat of an extended war. Adolescents are a sensitive group in society. They go through many changes at their age and are in the process of revealing their feelings and forming their worldviews. The study aimed to investigate how war events in Ukraine affected Lithuanian adolescents’ everyday life, relationships, health, attitudes, concentration, and learning. Materials and methods: Adolescents in 6 high schools filled out an anonymous Google Forms survey developed by the authors comprising general data about the respondent, their interest in war events and their involvement in following the news about the war in media, the impact of war events on their physical and mental health, and the feeling of fear about the threats of the war in Lithuania.  Results: 395 adolescents aged 16–19 (mean age 17.01±0.97) filled in the questionnaire. This research revealed that adolescents in Lithuania are moderately interested in war events in Ukraine, and 25.3% noted that they follow news about the war once a week. Most teenagers did not note that the ongoing war in Ukraine would affect their communication, ability to concentrate and learn, hobbies, appetite, and sleep. However, 48.9% indicated that war events affected their emotions and mood. Adolescents who talked about the ongoing war with their parents (55.4%, p=0.00006), who were more interested in war events in the media (median=229.7, p
Keywords: adolescents; teenagers; war; mental health; Ukraine; Lithuania